2022
DOI: 10.51386/25815946/ijsms-v5i2p109
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Leadership: A Literature Review

Abstract: Supportive Leadership study is needed since it is still difficult to discover past research that tackles the topic in depth. In addition, the goal of this research is to create a model for supportive leadership. Furthermore, to provide a clear image of themes linked to Supportive Leadership, this study used bibliometric order. The outcomes of this study show that each study places a different focus on the notion of supportive leadership. Acute stresses, creative culture, and leader workload are three more ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Likewise, those who are engaged in work feel more devoted to the organization, will be less likely to miss work, and not leave the organization. The effect of leadership style on the employees' competence and integrity is also confirmed in the studies of Dayanti et al, (2022) and Hafeez and Akhtar (2022). It was disclosed that while differing leadership styles may have an impact on the efficiency or productivity of a company, both work engagement and overall satisfaction are better predicted by transformational leadership.…”
Section: Figure 3 Emerging Modelmentioning
confidence: 56%
“…Likewise, those who are engaged in work feel more devoted to the organization, will be less likely to miss work, and not leave the organization. The effect of leadership style on the employees' competence and integrity is also confirmed in the studies of Dayanti et al, (2022) and Hafeez and Akhtar (2022). It was disclosed that while differing leadership styles may have an impact on the efficiency or productivity of a company, both work engagement and overall satisfaction are better predicted by transformational leadership.…”
Section: Figure 3 Emerging Modelmentioning
confidence: 56%
“…Being a supportive leader in the working environment means job satisfaction, productivity and high performance for employees (Kim et al, 2021). Incorporating employees into decision-making processes, resolving conflicts and maintaining the comfort of the working environment becomes possible if the leader is supportive in organizations (Dayanti et al, 2022). According to Generation Z, one of the significant qualities that an ideal leader should possess is that he supports, trusts and respects his employees (Aydoğdu and Kara Özkan, 2021;Gabrielova and Buchko, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They present the results of an empirical study conducted in six countries which fully or partially confirmed the importance of supportive leadership and job characteristics for lowering levels of workers' personal and social alienation. Dayanti et al (2022) review 16 publications on supportive leadership published from 2015 to 2020 and conclude that the term is most often used to describe leadership that helps subordinates to satisfy personal and work-related needs. Such leaders look after the well-being of employees, create a positive, comfortable, supportive work climate and relationships, and provide material, emotional, instrumental, and other support needed to do the work.…”
Section: Supportive School Leadership and Teacher Resiliencementioning
confidence: 99%